Reformasi Polri dan Refleksi Community Policing di Indonesia - Ramadhan, Gilang; Nurrohman, Bayu (Universitas Negeri Gorontalo, 2025)
Reforms open the tide of renewal in various lines, including the police institution as part of the State institution. The release of the Police from the TNI gave birth to the obligation of this institution to reform itself, increase professionalism and attention to human rights by leaving militaristic characteristics. This study uses a qualitative approach with a literature study method to elaborate on several existing writings with data to get in-depth writing about police reform. The conclusions of this paper to reform the police steps taken by reducing the level of violence and the use of firearms include the approach of community policing, besides being able to help reduce crime rates, it can also help increase public trust in the Police. In addition, using alternative weapons as a humane step and reducing casualties.